2014
DOI: 10.1017/s0265051714000138
|View full text |Cite
|
Sign up to set email alerts
|

Affordance of Braille music as a mediational means: significance and limitations

Abstract: Affordance refers to the properties or designs of a thing that offer the function of the thing. This paper discusses the affordance of Braille music in terms of three notions: mediational means, mastery and appropriation, and focuses on answering the following three questions: (i) How do musicians with visual impairments (MVI) perceive Braille music and what does it reveal about the characteristics and limitations of Braille music? (ii) What are the traits influencing the affordance of Braille music and how do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…Antoine began the semester without accessible music and attempted to accommodate himself by relying on what was available. Particularly for Antoine, the process of learning braille music was time-consuming and represented a barrier to his music teaching and learning, a finding supported by extant research (Abramo & Pierce, 2013;Lubet, 2004;Moss, 2009;Park & Kim, 2014). Though Lindsey's music was brailed prior to the semester's inception, she struggled when unexpectedly assigned a piece that was not accessible and self-accommodated using her digital recorder.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Antoine began the semester without accessible music and attempted to accommodate himself by relying on what was available. Particularly for Antoine, the process of learning braille music was time-consuming and represented a barrier to his music teaching and learning, a finding supported by extant research (Abramo & Pierce, 2013;Lubet, 2004;Moss, 2009;Park & Kim, 2014). Though Lindsey's music was brailed prior to the semester's inception, she struggled when unexpectedly assigned a piece that was not accessible and self-accommodated using her digital recorder.…”
Section: Discussionmentioning
confidence: 97%
“…Teachers with disabilities are important for diversifying the workforce and challenging perceptions of what it means to be able-bodied. In music education, researchers have focused on the experiences of individuals with visual impairments, including music teaching and learning within schools for the blind (Abramo & Pierce, 2013; Park & Kim, 2014) and one study of students with visual impairments enrolled in public school instrumental programs (Moss, 2009). In all inquiries, researchers found that using notation in musical contexts was secondary to sound.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In contexts such as this one, the mastery of Braille notation is extremely important for music learning (Chaves, 2014) and together with the use of assistive devices and technologies, is the main source of student autonomy (Egea, 2008). It enables them to understand music theory, compose, learn repertoire (Baker, 2014), and feel and create their own music, instead of just imitating the sounds they hear (Park & Kim, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the Braille code has been revised into a more simplified and efficient form so that the users could easily recognise letters with fewer touches (Olstrom, 2010). Nonetheless, as Braille music is not easy to learn or convenient to use, only few people with visual impairment utilise it.…”
Section: Introductionmentioning
confidence: 99%